Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.heliyon.2016.e00206
|View full text |Cite
|
Sign up to set email alerts
|

Understanding molecular markers in recurrent oral squamous cell carcinoma treated with chemoradiation

Abstract: IntroductionOral cancer accounts for approximately 2.1% of all cancers worldwide. In India, oral squamous cell carcinoma (OSCC) is the most common cancer with half a million new cases diagnosed every year. More than 50% of patients eventually develop local recurrence or metastasis usually within the first 2-years following completion of treatment. It is beneficial to analyze the prognostic significance of Cyclin D1, p53 and EGFR which are critical mediators in the pathogenesis of OSCC. The objective of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The majority of our patients were living (57%) at the end of follow up and recurrence was observed in 65% of the total. Authors also report a 5-year survival rate of 40-50% [48] with 50% of patients developing recurrence within the first two years of treatment [4]. We determined that EGFR significantly and independently affected 5 year survival and recurrence, with EGFR positive patients having markedly lower survival rates and increased chances of recurrence.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The majority of our patients were living (57%) at the end of follow up and recurrence was observed in 65% of the total. Authors also report a 5-year survival rate of 40-50% [48] with 50% of patients developing recurrence within the first two years of treatment [4]. We determined that EGFR significantly and independently affected 5 year survival and recurrence, with EGFR positive patients having markedly lower survival rates and increased chances of recurrence.…”
Section: Discussionmentioning
confidence: 81%
“…In accordance with our study, Gupta et. al also showed that EGFR overexpression was significantly related to recurrence and added that it also meant an early time to recurrence [4]. Moreover, an improved disease-free interval has been observed with low levels of EGFR accompanied by chemoradiation [33].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The changes in the expression of proteins related to the cell cycle, apoptosis, and angiogenesis were shown to affect radiosensitivity of OSCC and HNSCC patients . For example, overexpression of Cyclin D1, EGFR and p53 was associated with resistance to chemoradiation, the risk of locoregional recurrence and metastasis in OSCC patients …”
Section: Discussionmentioning
confidence: 99%
“…OSCC accounts for more than 90% of all oral cancers, in addition to exhibiting particularly high incidence and mortality rates. [20][21][22] Thus, this study aimed to examine the effect of TET1 and MGMT in regards to the chemotherapy sensitivity of OSCC stem cells. Through a series of well conducted and controlled experiments, it was ultimately concluded that low-expressed TET1 in OSCC stem cells could stimulate MGMT promoter methylation, thus strengthening the sensitivity of OSCC stem cells to chemotherapeutic drugs, which would as a result largely enhance treatment methods for patients suffering from OSCC.…”
Section: Discussionmentioning
confidence: 99%